2008
DOI: 10.3310/hta12120
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost-effectiveness of central venous catheters treated with anti-infective agents in preventing bloodstream infections: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 90 publications
2
66
0
3
Order By: Relevance
“…Median (15) time from referral to actual AVF procedure was 79 days and 57 days thereafter for AVF maturation (until first successful cannulation). Seven patients (8.8%) died during the follow-up period and were removed from the analysis at the time of their death.…”
Section: Definitive Accessmentioning
confidence: 99%
“…Median (15) time from referral to actual AVF procedure was 79 days and 57 days thereafter for AVF maturation (until first successful cannulation). Seven patients (8.8%) died during the follow-up period and were removed from the analysis at the time of their death.…”
Section: Definitive Accessmentioning
confidence: 99%
“…Veenstra et al published in 1999 a meta-analysis, which included 11 RCTs and 2,603 catheters, reporting that catheters impregnated with CHSS on the external surface (first generation) reduced the risk of CRBSI compared with non-impregnated catheters (28). Later, a meta-analysis published in 2008 by Hockenhull et al, including 3 RCTs and 1,176 patients, reported that catheters impregnated in CHSS on external and internal surfaces (second generation) reduced the CRBSI incidence compared to standard catheters (29). In addition, in a meta-analysis by Falagas et al published in 2007, including 3,452 CVCs from 8 RCTs (using rifampicin-minocycline impregnated catheters in 7 RCTs and rifampicin-miconazole impregnated catheters in 1 RCT), was found a reduction of CRBSI with the use of antimicrobial impregnated catheters compared with non-coated catheters (30).…”
mentioning
confidence: 99%
“…In addition, in a meta-analysis by Falagas et al published in 2007, including 3,452 CVCs from 8 RCTs (using rifampicin-minocycline impregnated catheters in 7 RCTs and rifampicin-miconazole impregnated catheters in 1 RCT), was found a reduction of CRBSI with the use of antimicrobial impregnated catheters compared with non-coated catheters (30). Besides, the use of antimicrobial impregnated catheters has been found to reduce the catheter related cost in some cost-effectiveness analyses (29,31,32). However, in all those cost-effectiveness analyses was included the cost associated with the increase of hospital stay.…”
mentioning
confidence: 99%
“…[1][2][3] Approximately 250000 cases of intravascular catheter-related bloodstream infections occur in the United States each year, resulting in a mortality of between 12-25% with an estimated cost of treatment per episode of approximately $25000. [3][4][5][6][7][8][9][10] The standard management of catheter-related infection involves decisions regarding removal of the catheter and the administration of appropriate antibiotics. Catheter removal and eventual replacement, raises important practical problems in these patients requiring parenteral nutrition, chemotherapy, and hemodialysis, among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that the high rate of therapy failure is explained in part by the inability of most antibiotics to kill bacteria growing in a biofilm. 3,6,[9][10][11][12][13][14][15] Certain infections now thought to be associated with biofilms, including otitis media, urinary tract infections, periodontitis, and burn infections, have been effectively treated with phage therapy. [16][17][18] Phage therapy has also been proposed to be used against multidrug-resistant bacteria, and may reduce the use of antimicrobial drugs and the spread of antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%